Traffic Performance Analysis of Jalan Rahadi Usman and Jalan Khatulistiwa Concerning the Garuda Bridge Development Plan in Pontianak - Siagian, Rita Apriliyani; Said, Said; Sumiyattinah, Sumiyattinah (Jurnal Teknik Sipil, 2025)
The separation between Pontianak Utara and Pontianak Kota Districts, previously connected via the Bardan"“Siantan ferry crossing, has led to long travel times and reduced mobility efficiency. To address this, the government plans to construct the Garuda Bridge as a replacement for the ferry, enhancing transportation safety, comfort, and efficiency. This infrastructure change is expected to influence traffic performance, requiring a comprehensive analysis. This study applies a four-step transportation model, with traffic load distribution in the assignment stage conducted using PTV Visum 2024. Model calibration employed the Least Squares method, while validation used the Chi-square method. Road capacity and peak-hour volume calculations were based on the Indonesian Highway Capacity Manual (PKJI) 2023. Findings indicate that, under existing conditions (2024), the Level of Service (LOS) falls into category C, with a degree of saturation of 0,53 and an average speed of 32,5 km/h. After the Garuda Bridge becomes operational in 2027, the LOS improves to category B, with a degree of saturation of 0,29 and an average speed of 42,7 km/h. The five-year projection (2032) shows the LOS remains in category B, with a degree of saturation of 0,34 and an average speed of 35,75 km/h, demonstrating sustained good road performance.